The origin of sin Greece and Rome, early Judaism and Christianity - Konstan, David 1940-2024 (London Bloomsbury Publishing Plc, 2022)
Cover page -- Halftitle page -- Series page -- Title page -- Copyright page -- Dedication -- Contents -- Preface -- Acknowledgments -- 1 The Greco-Roman World: The Unwritten Laws of the Gods -- 2 The Hebrew Bible: Chasing after Foreign Gods -- 3 The New Testament: Jesus' Sense of Sin -- 4 The Church Fathers and the Rabbis: The Transformation of Sin -- A Final Word -- Notes -- References -- Index.
Description based on publisher supplied metadata and other sources
Keywords: Sin-Christianity-History of doctrines; Sin-Biblical teaching; Sin; Electronic books